2020
DOI: 10.5101/nbe.v12i1.p104-113
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Photocatalytic Activity of Silver Nanoparticle Synthesized from Ehretia laevis Roxb. Leaves Extract

Abstract: Silver nanoparticles were synthesized from Ehretia laevis Roxb. leaf extract by one-step green synthesis method. The nanoparticles were crystalline in nature, spherical shaped with 25 to 35 nm diameter. The aim of this study was the synthesis and characterization of silver nanoparticles from Ehretia laevis Roxb., and the evaluation of their antimicrobial, anticancer, larvicidal and methylene blue dye degradation efficiency. The nanoparticles showed antimicrobial, larvicidal and cytotoxic activity. At a concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The absorption peak in the UV spectrum at 418.5 nm was observed pointing to the existence of a homogeneous shape after adding the filtrate of fungal biomass to the solution of silver nitrate, where the known color of Silver nanoparticle solution has brown color or dark reddish color with a difference in peak range between 400 nm to 480 nm [9] (Fig. 1 ).…”
Section: Biosynthesis Of Silver Nanoparticles Using L Lecanii Filtratementioning
confidence: 99%
“…The absorption peak in the UV spectrum at 418.5 nm was observed pointing to the existence of a homogeneous shape after adding the filtrate of fungal biomass to the solution of silver nitrate, where the known color of Silver nanoparticle solution has brown color or dark reddish color with a difference in peak range between 400 nm to 480 nm [9] (Fig. 1 ).…”
Section: Biosynthesis Of Silver Nanoparticles Using L Lecanii Filtratementioning
confidence: 99%
“…The median lethal concentration of the nanoparticles versus HeLa, human cervical cancer cells, and MCF-7 human breast cancer cells, were calculated to 12.7 μg/mL and 14.5 μg/mL, respectively. It possessed biological activities like cytotoxicity, larvicidal activity, and antimicrobial activity to some extent [43] .…”
Section: Plant Originmentioning
confidence: 99%
“…(all belonging to the Apocynaceae family). , A biological investigation showed that both the CHCl 3 and EtOH extracts of the leaves, roots, seeds, and stems of C. dubia exhibited activity against the bacteria Staphylococcus citreus and Shigella flexneri , and another study demonstrated that the MeOH extract of its stems showed analgesic, anti-inflammatory, and chondroprotective effects . In addition, the EtOH extract of the roots of C. dubia exhibited potent in vivo immunostimulant activity while its aqueous root extract showed hepatoprotective activity in mice. , Also, silver nanoparticles prepared from the water extract of the leaves of C. dubia showed cytotoxicity against human HeLa cervical and MCF-7 breast cancer cells …”
mentioning
confidence: 99%
“…6,7 Also, silver nanoparticles prepared from the water extract of the leaves of C. dubia showed cytotoxicity against human HeLa cervical and MCF-7 breast cancer cells. 8 Thus far, several cardiac glycoside epoxides have been identified from C. dubia, of which the structure of cryptosin isolated from the leaves of C. dubia has been determined by analysis of its single-crystal X-ray diffraction data. 9−11 Similar to other cardiac glycosides, cryptosin was found to show cardiotonic action, 10 and it also binds to Na + /K + -ATPase (NKA) and inhibits its activity.…”
mentioning
confidence: 99%